2012
DOI: 10.1007/s10464-012-9559-x
|View full text |Cite
|
Sign up to set email alerts
|

Testing Effects of Community Collaboration on Rates of Low Infant Birthweight at the County Level

Abstract: Interorganizational collaboration has become a popular strategy for addressing population health and well-being. However, evidence for its effectiveness in achieving outcomes at the population level is limited, at least in part due to a variety of methodological challenges such as reduced sample size at the population level, the availability of suitable comparison groups of communities, and study durations that are too short to detect slowly emerging outcomes. The present study addresses these challenges by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…These approaches reflect a commitment to engaging communities in developing and implementing structural solutions to local and population-specific concerns (Roussos and Fawcett 2000; Zakocs and Edwards 2006). By mobilizing collectives to engage in critically analyzing the root causes of local problems, identifying an array of potential solutions, developing multi-sector partnerships, and implementing strategies for creating local change, community mobilizations are demonstrated to strengthen communities and make them more health-promoting environments (Allen et al 2013; Cheadle et al 2008; Darnell et al 2013; Emshoff et al 2007; Javdani and Allen 2011; Salazar et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…These approaches reflect a commitment to engaging communities in developing and implementing structural solutions to local and population-specific concerns (Roussos and Fawcett 2000; Zakocs and Edwards 2006). By mobilizing collectives to engage in critically analyzing the root causes of local problems, identifying an array of potential solutions, developing multi-sector partnerships, and implementing strategies for creating local change, community mobilizations are demonstrated to strengthen communities and make them more health-promoting environments (Allen et al 2013; Cheadle et al 2008; Darnell et al 2013; Emshoff et al 2007; Javdani and Allen 2011; Salazar et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Several methodological challenges exist (Darnell et al 2013). These include an underspecified theory of community change, the lack of comparison groups to help rule out alternative hypotheses, lack of random assignment to comparison and experimental conditions, limited temporal ordering, the absence of outcome assessments by independent reporters that can be compared against predetermined criteria, inadequate sample sizes for detecting effects, and low response rates to surveys (often as low as 35–44 %; rarely over 67 %) that may render samples non-representative (Allen 2005; Florin et al 1993, 2000; Merzel and D’Afflitti 2003; Kegler et al 2005; Kumpfer et al 1993; Rogers et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Another study examined longitudinal change in population level rates of low infant birthweight among counties collaboratives targeting this outcome for two or more years. The findings suggested that targeting counties had smaller increases in low infant birthweight than statistically matched comparison counties (Darnell et al 2013). The findings from these two studies provide empirical support for GaFCP model of community collaboration.…”
Section: Gafcp and Community Collaborationmentioning
confidence: 96%
“…Based on this needs assessment process, the collaborative develops and implements a plan to address the identified needs. Further information on the GaFCP model of collaboration is available via its website (www.gafcp.org) and in recent publications (e.g., Barile et al 2012;Darnell et al 2013;Emshoff et al 2007). …”
Section: Gafcp and Community Collaborationmentioning
confidence: 99%
See 1 more Smart Citation